EVALUATION OF WASTEWATER MANAGEMENT SYSTEMS IN ABUJA FOR SUSTAINABILITY AND DEVELOPMENT OF APPROPRIATE ENGINEERING STRATEGY (2013)
Environmental pollution due to improperly managed wastewater has been a major challenge and of public health concern in Nigeria. Not many studies related to wastewater management have been carried out in Nigeria, hence the paucity of data on wastewater management in the country. The Wastewater Treatment Plants (WTP) in Nigeria's capital city, Abuja are presently performing below capacity due to several problems. The aim of this study was to evaluate the wastewater management system for Abuja and develop an engineering strategy to improve it. Six WTPs at Wuye lagoon, Gudu, Niger, Lungi, Mogadishu barracks and Sheraton were assessed in comparison with the existing wastewater Master Plan of Abuja. The sites were visited along with their sewer lines and manholes to assess their structural and environmental engineering adequacy. Influent and effluent samples were collected weekly from these plants at peak period in the morning hours (6.00 - 7.00am) in triplicates over six months period from October 2007 to March 2008. These samples were analyzed for quality parameters such as 5-Day Biochemical Oxygen Demand (BOD5), Chemical Oxygen Demand (COD), nitrate, nitrite, sulphate, chloride, phosphate, and microbial content. Data were further analysed using ANOVA at p= 0.05. Based on the evaluation, a suitable wastewater treatment plant was designed. These WTPs are mini activated sludge treatment plants with submersible mechanical aerators. Wuye lagoon has a capacity of 50,000 Population Equivalent (PE). Gudu, Lungi and Mogadishu barracks have 6000 PE each while Niger and Sheraton have 3000 PE each. Average reduction of BOD5 of 6±50.2%, 4±25.8%, 30±0.8%, 10.2±0.2%, 10.8±24.9% and 5±39.6% were observed for Wuye lagoon, Gudu, Mogadishu, Niger, Lungi and Sheraton respectively. For other evaluated parameters, average reduction in COD, nitrate, sulphate, chloride, phosphate and microbial quality were 7.8±12.4%, 13.1±4%, 13.5±65.4%, 21.5±89.8%, 10.1±8.4% and 48±87.9% respectively. Sludge treatments significantly affect the physico-chemical parameters. No regular aeration was carried out in the plants. In the satellite towns of Gwagwalada, Kuje, Kubwa and Nyanya, there were no sewer facilities, hence septic tanks and soak-away pits were constructed to handle the generated wastewater which is contrary to the provisions of Abuja Master Plan. Non-biodegradable substances such as nylon and plastics were observed in manholes. Discharge of evacuated septic sludge into sewer lines was the practice. A wastewater treatment plant combining both natural and electromechanical system was designed (Design flow of 2070 m3/d, BOD5 of 517Kg/day and Suspended Solids of 517.5kgSS/day). The treatment plant using water hyacinth yielded nutrient removal of about 70.0% when power is not available and enhanced treatment of up to 99.0% BOD removal when power is available. The designed wastewater treatment plant using appropriate engineering strategy was adequate and capable of solving the wastewater management problems of Abuja. The design would be useful in other major cities in Nigeria.